2018
DOI: 10.3390/ijms19092496
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Exploration of Selectivity of Dual Inhibitors 5M7, 65X, and 65Z toward Fatty Acid Binding Proteins 4 and 5

Abstract: Designing highly selective inhibitors of fatty acid binding proteins 4 and 5 (FABP4 and FABP5) is of importance for treatment of some diseases related with inflammation, metabolism, and tumor growth. In this study, molecular dynamics (MD) simulations combined with molecular mechanics generalized Born surface area (MM-GBSA) method were performed to probe binding selectivity of three inhibitors (5M7, 65X, and 65Z) to FABP4/FABP5 with Ki values of 0.022/0.50 μM, 0.011/0.086 μM, and 0.016/0.12 μM, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 91 publications
(93 reference statements)
0
21
0
Order By: Relevance
“…The study subject was FABP4—a newer adipokine which appears to be involved in the pathophysiology not only of GDM but also of adiposity, insulin resistance, T2DM, atherosclerosis, hypertension, coronary artery and cerebrovascular diseases, and metabolic syndrome [18,21,22,23,24,25,26,29,30]. In our previous study, we concluded that FABP4 seems to be an “inauspicious”/a proinflammatory adipokine [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study subject was FABP4—a newer adipokine which appears to be involved in the pathophysiology not only of GDM but also of adiposity, insulin resistance, T2DM, atherosclerosis, hypertension, coronary artery and cerebrovascular diseases, and metabolic syndrome [18,21,22,23,24,25,26,29,30]. In our previous study, we concluded that FABP4 seems to be an “inauspicious”/a proinflammatory adipokine [18].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, animal models deficient in FABP4 present reduced hyperinsulinemia and insulin resistance in obesity, which is suggestive of this adipocytokine’s effect on the interdependence between obesity and insulin resistance [20]. FABP4 appears to be one of the most probable candidates involved in the pathophysiology of GDM [21], as well as adiposity, insulin resistance, type 2 diabetes mellitus (T2DM), atherosclerosis, hypertension, coronary artery, cerebrovascular diseases, and metabolic syndrome [22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…This newer adipokine appears to be one of the most probable candidates involved in the pathophysiology of GDM, similarly to well-known and verified markers of diabetes and obesity, such as adiponectin, leptin, and tumour necrosis factor α (TNFα) [11,12,13]. Furthermore, the roles of FABP4 in the development of adiposity, insulin resistance, T2DM, atherosclerosis, hypertension, coronary artery and cerebrovascular diseases, as well as metabolic syndrome, are of great concern [14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Relative contributions, but on a smaller scale of the hydrogen bond, and cation‐π and π‐π interactions were also detected. [ 57,58 ]…”
Section: Resultsmentioning
confidence: 99%